2021
DOI: 10.1002/cpdd.895
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Pharmacodynamics of a Dipeptidyl Peptidase‐4 Inhibitor: A Randomized, Double‐Blinded, Placebo‐Controlled Daily Administration of Fotagliptin Benzoate for 14 Days for Type 2 Diabetes Mellitus

Abstract: This study investigated the pharmacokinetics, pharmacodynamics, and safety of fotagliptin benzoate (fotagliptin), a dipeptidyl peptidase-4 (DPP-4) inhibitor, in Chinese patients with type 2 diabetes mellitus (T2DM). In a randomized, doubleblinded, placebo-controlled study, 10 and 4 patients with T2DM were randomized and received, respectively, once-daily oral fotagliptin (24 mg) or placebo, for 14 days. The pharmacokinetics and pharmacodynamics were assessed throughout the study, including monitoring DPP-4, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These may be attributed to the pharmacokinetic and pharmacodynamic results of both fotagliptin and alogliptin. One recent study in Chinese patients with T2DM indicated that fotagliptin could increase plasma GLP-1 concentration while DPP-4 inhibition was continuously maintained at a steady state [ 12 ]. Still, relevant results were based on the design of the study and patients were closely monitored to ensure that they followed the diet and exercise guidelines of the trail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These may be attributed to the pharmacokinetic and pharmacodynamic results of both fotagliptin and alogliptin. One recent study in Chinese patients with T2DM indicated that fotagliptin could increase plasma GLP-1 concentration while DPP-4 inhibition was continuously maintained at a steady state [ 12 ]. Still, relevant results were based on the design of the study and patients were closely monitored to ensure that they followed the diet and exercise guidelines of the trail.…”
Section: Discussionmentioning
confidence: 99%
“…Fotagliptin was not primary metabolized by cytochrome P450 enzymes. There were 2 major metabolites, M1 had no inhibitory effect on DPP-4, M2-1 had slight inhibition [ 12 ]. The efficacy and safety profiles of fotagliptin have been characterized in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shu et al from XuanZhu Pharma identified compound 65 (imigliptin, DPP-4 IC 50 = 9.0 nM) via a scaffold-hopping approach from alogliptin, which is a highly selective and oral active DPP-4 inhibitor entering into phase II clinical trials . Fosun Pharma reported a 5-oxo-1,2,4-triazine derivative 66 (fotagliptin, DPP-4 IC 50 = 2.2 nM) in phase III clinical trials in China. , Xie et al reported a pyrrolopyrimidine analogue 67 as a potent DPP-4 inhibitor (DPP-4 IC 50 = 1.4 nM) with greater in vivo efficacy than alogliptin . Wu et al from Merck designed the tricyclic heterocycle 68 as a potent DPP-4 inhibitor (DPP-4 IC 50 = 1.7 nM) that demonstrated robust glucose-lowering efficacy after oral administration in mice and potential for a long duration of action .…”
Section: Structural Evolution From Lead Compounds To Long-acting Dpp-...mentioning
confidence: 99%